Objects and Events as Determinants of Parallel Processing in Dual Tasks: Evidence From the Backward Compatibility Effect. - Ellenbogen, Ravid; Meiran, Nachshon (Journal of Experimental Psychology. Human Perception & Performance, 2011)
The backward-compatibility effect (BCE) is a major index of parallel processing in dual tasks and is related to the dependency of Task 1 performance on Task 2 response codes (Hommel, 1998). The results of four dual-task experiments showed that a BCE occurs when the stimuli of both tasks are included in the same visual object (Experiments 1 and 2) or belong to the same perceptual event (Experiments 3 and 4). Thus, the BCE may be modulated by factors that influence whether both task stimuli are included in the same perceptual event (objects, as studied in cognitive experiments, being special cases of events). As with objects, drawing attention to a (selected) event results in the processing of its irrelevant features and may interfere with task execution. Reprinted by permission of the publisher.